Transcultural media practices fostering cosmopolitan ethos in a digital age: engagements with East Asian media in Australia. Issue 1 (2nd January 2020) - Martin, Fran; Iwabuchi, Koichi; Gassin, Grace; Seto, WaiLing
ABSTRACT: The increasingly transnational reach of East Asian media suggests that East Asia has become an ever more de-territorialized media zone. But what has been relatively neglected in the extant scholarship is in-depth consideration of how East Asian media culture has been transnationalised beyond the geographic boundaries of Asia, especially in the context of accelerating online content distribution. In this article, we propose that Australia provides a useful case study to illuminate the cultural impacts of East Asian media beyond Asia. What is Australia's place in trans-Asia media circuits? Does the consumption of East Asian media by audiences in Australia enable them to develop increasingly reflexive understandings of cultural identity, in a turn toward everyday cosmopolitanism? Alternatively, might the new kind of mediasphere we witness emerging in Australia entail new forms of cultural encapsulation, or a proliferation of mutually disconnected ethno-specific media sphericules? Analysing in-depth qualitative interviews with 47 users of East Asian media in Australia, this article investigates how such media engagements open up and/or close down routes to reflexive transcultural practices for these media users; that is, it evaluates the potential of these media to cultivate cosmopolitan ethos in this context. We conclude that East Asian media in Australia may function for their users, paradoxically, as a cosmopolitan media niche within a national mediascape characterised more typically by cultural encapsulation.